2005
DOI: 10.1073/pnas.0503473102
|View full text |Cite
|
Sign up to set email alerts
|

AtCCMH, an essential component of thec-type cytochrome maturation pathway inArabidopsismitochondria, interacts with apocytochromec

Abstract: The maturation of c-type cytochromes requires the covalent ligation of the heme cofactor to reduced cysteines of the CXXCH motif of apocytochromes. In contrast to mitochondria of other eukaryotes, plant mitochondria follow a pathway close to that found in ␣-and ␥-proteobacteria. We identified a nuclear-encoded protein, AtCCMH, the Arabidopsis thaliana ortholog of bacterial CcmH͞CycL proteins. In bacteria, CcmH and the thioredoxin CcmG are components of a periplasmic thio-reduction pathway proposed to maintain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 39 publications
4
99
0
Order By: Relevance
“…Earlier, the ability of E. coli CcmH to reduce in vitro a disulfide bond formed at the heme binding site of an apocytochrome c-like peptide was reported (10,42). Also, using a yeast two-hybrid system, the interactions in vivo between Arabidopsis thaliana CcmH or CcmFN2 and apocytochrome c were described (43). More recently, in vitro weak binding of apocytochrome c 2 to a Cys-less CcmG protein was detected (23).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, the ability of E. coli CcmH to reduce in vitro a disulfide bond formed at the heme binding site of an apocytochrome c-like peptide was reported (10,42). Also, using a yeast two-hybrid system, the interactions in vivo between Arabidopsis thaliana CcmH or CcmFN2 and apocytochrome c were described (43). More recently, in vitro weak binding of apocytochrome c 2 to a Cys-less CcmG protein was detected (23).…”
Section: Discussionmentioning
confidence: 99%
“…A number of plant mutants lacking respiratory chain components have been studied, including mutants in complex I (Marienfeld and Newton, 1994;Pla et al, 1995;Lee et al, 2002;Perales et al, 2005) and mutants removing specific nonphosphorylating bypasses such as AOX (Giraud et al, 2008). Mutants lacking complex II are embryo lethal in plants (Leon et al, 2007) and mutants lacking complex III or IV have not been reported, presumably as these are lethal in plants, as are mutants in the assembly of c-type cytochromes (Meyer et al, 2005).…”
mentioning
confidence: 99%
“…However, although ccmBCF orthologs are conserved on all mitochondrial genomes of land plant, ccmA could not be found on any of them. The sequence similarity between CcmA and the nuclear encoded NAP10 strongly suggests that ccmA has been transferred to the nucleus as shown in A. thaliana for genes encoding two other plant mitochondrial CCM proteins, the heme chaperone AtCCME (23), and the thiol-disulfide oxidoreductase AtCCMH (24). In this work we show that NAP10 is a mitochondrial protein, which has kept the topology of its bacterial counterpart CcmA and has characteristics of the NBD of an ABC transporter.…”
mentioning
confidence: 80%
“…However, AtCCMA failed to complement a deletion mutant of E. coli ccmA for the production of holocytochrome c. The complexity of transient interactions between Ccm proteins in bacteria could explain this negative result. Indeed in different complementation assays performed in E. coli with Arabidopsis proteins no functional complementation could be obtained (23,24). The interaction between the chimeric ABC transporter and the heme chaperon CcmE could be affected.…”
Section: Discussionmentioning
confidence: 99%